COMPARATIVE ANALYSIS OF LABORATORY LESSON EFFICIENCY BASED ON TIME CRITERION - Turdaliyev Ulugbek (Bright Mind Publishing, 2025)
This article addresses the issue of increasing the effectiveness of laboratory classes in teaching physics in general education schools. Experimental lessons conducted using traditional equipment and newly developed modern laboratory kits were comparatively analyzed through the time criterion. The research results show that the use of innovative didactic tools provides an opportunity to perform experiments faster, more accurately, and more clearly, increases students' interest in science, and helps them consciously assimilate knowledge. This article substantiates ways to improve the quality of lessons and the effectiveness of the educational process by integrating modern technologies into physics classes.
Keywords: physics education, laboratory lesson, modern laboratory kit, traditional equipment, time efficiency, didactic tool, learning activity, innovative technologies, experimental analysis, student engagement